Diseño de control interno aplicando el método coso en la agrícola bananera Laurita del cantón La Maná, provincia de Cotopaxi, año 2010 - Jácome Vivas, Rosa Maricela (2012)
The research conducted had as main objective to provide the implementation of internal control implies that each of its components is applied to a business essential category of becoming an inclusive and dynamic process. Is why this thesis is that the Banana Agricultural Laurita run the method, with the help of the theoretical foundation, it will help the development of the proposal….